Carbon Nanotube Fibers: Chemically Reactive Polyurethane–Carbon Nanotube Fiber with Aerogel‐Microsphere‐Thin‐Film Selective Filter (Adv. Mater. Interfaces 20/2018). Issue 20 (23rd October 2018) - Jeong, Sang‐Mi; Kang, Youngsoo; Lim, Taekyung; Ju, Sanghyun
Abstract : The aerogel–microsphere–thin‐film, which can block liquid volatile organic compounds/water and allows only volatile organic compound vapor to permeate, is introduced to the surface of the sensing channel of the chemically reactive polyurethane–carbon nanotube composite fiber‐type chemical sensor. This is reported by Sang‐Mi Jeong, Sanghyun Ju, and co‐workers in article number1800935 .